Qualitative analysis and environmental impact from Photovoltaic Energy use: 3 Peruvian study cases - Sánchez Talledo, Dairo Alejandro (2023)
The objective of this article is to analyze and measure the environmental impact from the photovoltaic energy use through three photovoltaic systems that already exist in Peru. To reach that an energy balance or energy payback time (EPBT) calculation and a carbon footprint sizing was made. For the analysis, the stage of manufacture, transport, installation and uninstallation of solar panels was considered, furthermore, the manufacture of the elements from the Balance of System (BOS) that contribute significantly to the life cycle of the solar panels.  The first case is a group of 5 rural houses at Puno that consume 10 kWh/day. The second case is the photovoltaic system that is installed at the Institute of Mining Engineers of Peru roof and has a 20 kWp capacity. The third case is the Rubi Solar Central at Moquegua, which has a 179.5 MWp capacity. The EPBT obtain for the three cases are 4.68, 6.42 y 3.64 years, respectively. In addition, the produce carbon footprint of the photovoltaic systems was 11 tCO2eq, 71.41 tCO2eq y 0.57 MtCO2eq, respectively, through an own calculation tool.